Pengaruh Latihan Aerobik Dan Anaerobik Terhadap Profl Lipid Pada Tikus Rattus Norvegicus Wistar - Budijanto Budijanto (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2018)
Doing exercises regularly is useful to help improve strength, frmness, and endurance and also to avoid early aging process The best exercises to make body healthy are swimming, quick hiking, jogging, and cycling. The goal of the research was to verify the difference of inﬂuence toward aerobic and anaerobic exercises towards the change of cholesterol, cholesterol HDL and LDL as well as ratio of cholesterol HDL and LDL. The research was experimental using post test and control group. The sample was classifed into three groups, each of which consisting 10 mice and then randomly aerobic and anaerobic exercises and control group were done. The aerobic exercise by swimming used 3% burden of body weight for 13 minutes and the anaerobic exercise 9% for 0ne minute by taking rest for 3 minutes intermittently as many as 4 sets, while control group did it without exercise. Based on the data analysis, it was found that aerobic exercises was effective to reduce cholesterol, improve cholesterol of HDL and LDL, and ratio of cholesterol of HDL and LDL. In addition the aerobic exercise was better than anaerobic exercise